Embodied Listening: Disrupting Speech-as-Presence towards Imaginative Ways of Being in the Classroom - Hanrahan, Kelsey B.; Billo, Emily (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
In this paper, we propose embodied listening as pedagogical praxis in which we are receptive to how our whole bodies are involved in communicating with each other. Embodied listening disrupts what we call “speech-as-presence”—normative expectations of student participation emphasizing verbal contributions and privileging particular bodies. These expectations contribute to the reproduction of oppressive logics at work in classrooms—racism, hetero-patriarchy, white feminism, masculinism, ableism, colonialism. We argue that embodied listening can serve as a source of knowledge about these logics, supporting transformation of classroom expectations beyond imposed norms. We reflect on our experiences developing embodied listening practices in our undergraduate courses through our observations and students’ own reflections. Our findings demonstrate both the transformative potential of listening in classrooms and the tensions produced as these strategies discomfited students and disrupted classroom norms. Finally, we engage with critical perspectives on listening positionality from Indigenous studies, disability studies, and sound studies towards deepening our understanding of differences and multiplicities in how we listen. We illustrate how we continue to develop ways to incorporate this work in our classrooms and support students in the exhaustive and uncomfortable work of embodied listening and imaginative ways of being in the classroom.